Traumatic Brain Injury Patients in the Emergency Unit of a Tertiary Hospital - Zairinal, Ramdinal Aviesena; Malufti, Chandrika Najwa; Ramli, Yetty; Lastri, Diatri Nari; Mayza, Adre; Prawiroharjo, Pukovisa (Folia Medica Indonesiana, 2023)
Highlights: 1. The main focus of this study was to underscore the importance of exploring the characteristics of traumatic brain injury (TBI) patients, which have not been extensively investigated, to help establish effective clinical procedures and decisions. 2. Three out of every four trauma patients in the emergency unit had mild TBIs, and those who did not survive showed a significant trend of rapid deterioration. 3. It is crucial to consistently conduct a thorough and comprehensive head-to-toe examination for all trauma patients. Abstract Traumatic brain injury (TBI) is a prevalent neurological condition in emergency units. TBI cases are frequently diagnosed with severe conditions. Underdiagnosis is common in mild TBI cases. As a result, physicians have an uncomprehensive understanding of the patients' characteristics in their daily practice. This study aimed to discuss the characteristics of trauma patients who were diagnosed with TBIs in an emergency unit. We conducted a retrospective cohort observational study to examine the adult population of TBI patients from April 2022 to March 2023. This study collected several data points, including demographics, clinical characteristics, surgical procedures, and disposition distribution. All variables were compiled and summarized using descriptive statistics and analyzed by calculating frequencies and percentages. During the period of this study, 483 trauma patients were admitted to the emergency unit. A total of 361 (74.7%) of these cases were identified as TBIs. Most of the traumatic brain injuries occurred in men (75.6%), with the predominant age range being 18–22 years (22.4%). Mild TBI cases (74.5%) were the most prevalent, followed by moderate (20.2%) and severe (5.3%) TBI cases. The average score from the Glasgow Coma Scale assessment was 15. Most patients (80.9%) had no hypotension, while a greater number of patients (98.1%) did not exhibit hypoxia as a comorbidity. The Injury Severity Score revealed that the highest percentage of TBIs was categorized as minor (62.3%). It was found that 53.5% of the patients were discharged, while 36% of the patients were hospitalized. However, 7 patients (1.9%) passed in the emergency unit, and 30 patients (8.3%) opted to be discharged against medical advice. Only 21 patients (5.8%) received neurosurgical management. As the most prevalent trauma, TBI necessitates careful management to handle the implications of clinical decision-making. It is crucial to investigate the underlying risk of mortality in TBI cases because the majority of patients do not require neurosurgical intervention.